16‐O‐Methylated diterpenes in green Coffea arabica: ultra‐high‐performance liquid chromatography‐tandem mass spectrometry method optimization and validation. (6th August 2020) - Guercia, Elena; Colomban, Silvia; Navarini, Luciano
Abstract: Coffee diterpenes are the main constituents of the coffee oil unsaponifiable fraction. The three most important diterpenes are cafestol, kahweol, and 16‐ O ‐methylcafestol (16‐OMC), and they are produced, except for cafestol, only by plants of the Coffea genus. Recently, in addition to these three major diterpenes, another 16‐ O ‐methylated diterpene (16‐ O ‐methylkahweol: 16‐OMK) has been identified and quantified, for the first time, in Robusta coffee. For many years, 16‐OMC has been considered present exclusively in Robusta, and so it has been reputed an excellent authenticity marker for the presence of Robusta in coffee products. For its quantification, nuclear magnetic resonance (NMR) has proved very useful when compared with other methods. Quite recently, the detection of very low levels of the two 16‐ O ‐methylated diterpenes (16‐OMD) 16‐OMC and 16‐OMK in roasted Arabica was reported. This finding makes the use of NMR methods in 16‐OMD quantification in Arabica coffee particularly challenging in view of both the trace amounts of 16‐OMD and the impossibility to discriminate between 16‐OMC and 16‐OMK. The ultra‐high performance liquid chromatography mass spectrometry (UHPLC‐MS) method, already used to detect 16‐OMC and 16‐OMK in Arabica roasted coffee, is then more suitable for quantitative analyses. Up to now however, no quantification of coffee 16‐OMD via ultra‐high performance liquid chromatography tandem mass spectrometry (UHPLC‐MS/MS) has been carried out; this largely stimulated the present study. For the first time, a simple procedure for the quantitative detection of 16‐OMD in Arabica coffee has been developed, and as far as 16‐OMC is concerned, fully validated in terms of specificity, linearity, concentration range, limit of detection (LOD), limit of quantification (LOQ), and repeatability following the criteria specified in the EU Commission Decision 2002/675/EC. This method proved to be very specific and sensitive. In order to avoid the chemical complexity generated by the roasting process, the method was optimized and validated on several green Arabica samples from different geographical origins.